Analisis rata-rata lama sekolah dan pengeluaran per kapita sebagai pembentuk Indeks Pembangunan Manusia (IPM) di Kabupaten Tabalong - Tania Azahrah Salsa Bella; Suratno Martodiryo; Melly Agustina Permatasari; Monry Fraick Nicky Gillian Ratumbuysang (Universitas Negeri Surabaya, 2025)
This study examines the Human Development Index (HDI) as a primary indicator of human development quality, focusing on two core indicators: average years of schooling and per capita expenditure. It analyzes the comparison of these two indicators in Tabalong Regency during the period from 2012 to 2023, while taking into account income inequality as measured by the Gini Ratio and HDI classifications. A quantitative descriptive-comparative approach was employed. The data used is time series data from 2012 to 2023, consisting of secondary data obtained from the Central Statistics Agency (BPS) of Tabalong Regency. Data analysis was conducted using descriptive statistics and Independent t-Test with the assistance of IBM SPSS 25. The findings indicate that income inequality does not directly affect educational attainment or per capita expenditure, as reflected in these two indicators. Conversely, regions with higher HDI tend to show improvements in both average years of schooling and per capita expenditure. This study highlights the importance of integrated policy approaches in education, economic growth, and public health to promote inclusive and sustainable human development.